Research of electrical treatment of plant raw materials in vibroextraction - Zavialov, Volodymyr; Zaporozhets, Yuliia; Mysiura, Taras; Popova, Nataliia; Sukmanov, Valeriy; Chornyi, Valentyn (My University, 2018)
The paper presents the results of research on the influence of low-frequency mechanical oscillations and electric discharges on morphological changes in a structure of hop raw material for vibroextraction. Shown expedience of preliminary processing of water-hops suspension by electropulse discharges in order to intensify vibroextraction of plant raw material with low extractive property. Determined rational process parameters. Представлено результати досліджень впливу низькочастотних механічних коливань та електричних розрядів на морфологічні зміни структури хмелевої сировини при виброекстракції. Показано доцільність попередньої обробки водно-хмільної суспензії електроімпульсними розрядами з метою інтенсифікації вібекстрагування рослинної сировини з низькою екстрактивною властивістю. Визначено раціональні параметри процесу.
Keywords: extraction; plant raw materials; electroprocessing; extraction curves; hop raw material; kinetics of process; екстрагування; рослинна сировина; електрообробка; екстракційні криві; хмелева сировина; кінетика процесу; кафедра процесів і апаратів харчових виробництв; кафедра експертизи харчових продуктів